Rare chromosomal aberrations detected in children with multiple congenital anomalies: utility of multiple ligation dependant probe amplification for developing countries. Issue 3 (12th April 2021) - Pulipaka, Shirisha; Kaur, Anit; Bhatia, Prateek; Panigrahi, Inusha; Kaur, Anupriya
Abstract : Chromosomal aberrations are an important cause of multiple malformation syndromes. Multiple ligation-dependent probe amplification (MLPA) a molecular cytogenetic technique has been suggested as a screening tool for the detection of chromosomal aberrations in resource-limited settings. MLPA can detect chromosomal microdeletions or duplications at approximately 40 chromosomal regions in a single experiment. Several MLPA kits are available to target the chromosomal regions of interest. In the present study, we aimed to detect the yield and utility of MLPA in a cohort of children with multiple malformations and developmental delay. MLPA was performed using kits P245, P070 and P036. The overall yield of MLPA in our cohort was 8%. The manuscript describes very rare and interesting cases of congenital anomalies, such as severe buphthalmos and biphalangeal fingers with a chromosomal etiology. The study demonstrates the usefulness of MLPA as screening technique for chromosomal aberrations in children with multiple malformation syndromes, especially for developing countries such as India.